2022
DOI: 10.1111/jcpe.13679
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of periodontitis grade in epidemiological studies using interdental attachment loss instead of radiographic bone loss

Abstract: Aim: Comparison of grading according to radiographic bone loss (BL) or according to interdental clinical attachment loss (CAL).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
(71 reference statements)
0
3
0
Order By: Relevance
“…In the absence of direct evidence of progression based on longitudinal CAL or BL measurements, or in the absence of any radiographic examination, indirect evidence of progression can be inferred (Winkler et al, 2022) by considering relative CAL as a percentage of the root length based on root length data provided by two studies (Salonen et al, 1991; Schumacher & Gente, 1995). While this seems to be an appealing method, grade assignment using CAL and standard root length data showed only fair to good/moderate agreement with the one based on relative BL data (kappa values ranged between 0.359 and 0.427) (Winkler et al, 2022). Thus, assessment of grade based on cross‐sectional CAL data in the absence of radiographs has apparent shortcomings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the absence of direct evidence of progression based on longitudinal CAL or BL measurements, or in the absence of any radiographic examination, indirect evidence of progression can be inferred (Winkler et al, 2022) by considering relative CAL as a percentage of the root length based on root length data provided by two studies (Salonen et al, 1991; Schumacher & Gente, 1995). While this seems to be an appealing method, grade assignment using CAL and standard root length data showed only fair to good/moderate agreement with the one based on relative BL data (kappa values ranged between 0.359 and 0.427) (Winkler et al, 2022). Thus, assessment of grade based on cross‐sectional CAL data in the absence of radiographs has apparent shortcomings.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that radiographic BL data are commonly unavailable in epidemiological surveys, relative CAL as a percentage of the root length can be estimated using the following formula: relative CAL (%) = 100 Â CAL (mm)/root length (mm). Root length data can be retrieved from two studies as suggested by Winkler et al (2022): standard root lengths of a German cohort were reported for all teeth without distinction between sexes (Schumacher & Gente, 1995), see also Appendix Table 1. Sex-specific root lengths from mesial and distal sites of all teeth (excluding third molars) were reported for 732 randomly selected Swedish males and females (Salonen et al, 1991), see also Appendix Table 2 Under the following link, information and syntax for various statistical programs implementing the ACES framework to epidemiological survey data will be provided: https://github.com/ACESperiodontitis.…”
Section: Assessment Of Gradementioning
confidence: 99%
“…Sample size calculation was done based on previous data as reported by Winkler et al [ 24 ] under the assumption of an expected kappa value of 0.4, a minimum acceptable kappa of 0.7 and a proportion of outcome (i.e. periodontal grade C according to radiographic bone loss) indicating a minimum sample size of 66 individuals to reach a power (1-β) of 0.9.…”
Section: Methodsmentioning
confidence: 99%